2021
DOI: 10.1212/cpj.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Advanced Practice Providers in an Academic Department of Neurology

Abstract: BackgroundIntegrating advanced practice providers (APPs) into neurological practice can improve access, promote patient education, and reduce healthcare costs. APPs receive limited formal education in neurology, so on-the-job training is essential. We set out to identify common challenges and best practices for onboarding, training, and integrating APPs into neurological practice.MethodsWe conducted a survey and focus group with eight APPs currently practicing within an academic neurology department as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recent data from focus groups has suggested that neuroimaging is a key knowledge gap for APPs practicing neurology. 2 This study adds to the mounting evidence that neuroradiology should be a target of postgraduate education for PAs. Although new graduates of PA programs should not be expected to be experts in interpreting neuroimaging, addition of neuroimaging basics to PA program curriculum, including indications for obtaining neuroimaging, may also benefit graduates practicing in specialties such as primary care and emergency medicine.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recent data from focus groups has suggested that neuroimaging is a key knowledge gap for APPs practicing neurology. 2 This study adds to the mounting evidence that neuroradiology should be a target of postgraduate education for PAs. Although new graduates of PA programs should not be expected to be experts in interpreting neuroimaging, addition of neuroimaging basics to PA program curriculum, including indications for obtaining neuroimaging, may also benefit graduates practicing in specialties such as primary care and emergency medicine.…”
Section: Discussionmentioning
confidence: 82%
“…Advanced practice providers (APPs) report limited neurologic education in their undergraduate degree programs, specifically identifying neuroradiology, neuroanatomy, and neurologic differential diagnosis as key knowledge gaps. 2,3 Efforts are already underway to enhance on-the-job training for recently graduated APPs, and some institutions have even created residency and fellowship programs for APPs interested in careers in neurology. 2,4,5 The success of these programs and the utility of educational resources developed for APPs starting careers in neurology critically depends on an accurate understanding of the educational needs of this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four main themes extracted from interview analysis highlight the important role that collaboration, education, support, and autonomy play in the success of the APP in practice. Previous related research examining best practices for integration of an APP into a specialty department of an academic institution supports this conclusion that a better understanding of the scope of practice of the APP, by both colleagues and patients, would benefit the role and its ability to function in the department (Gheihman et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…First, from both a previous study at our institution and our pre-implementation interviews, we identified that our APPs had a strong desire to see a wide-breadth of cases, including ones with increasing complexity. 11 APPs desired a level of autonomy similar to residents. This helps to promote their own education, job satisfaction, and reduces burnout.…”
Section: Discussionmentioning
confidence: 99%